Overview of Side Effects and How To Handle In 3-Month Injection KB Accepters - Ariu Dewi Yanti (Kirana Publisher (KNPub), 2023)
Hormonal contraceptives are the tools most often used, such as pills, injections and implants used by mothers. This hormonal contraceptive actually has various negative effects for its users. The side effects that are caused are indeed harmless, but later something will arise that is uncomfortable for the user. Such as menstrual cycle disturbances, fluctuating weight, nausea or vomiting, dizziness or headaches, pimples and black spots, even sexual dysfunction. These procedures affect reproductive health and well-being. The research used is to use a type of descriptive research (descriptive research), by describing the events that existed when the research took place which are natural in nature from the results of human engineering, through a quantitative approach. By showing the results of research regarding the age of respondents who use family planning aged 20 to 35 years, with a history of education at the elementary school level (SD) and an average of using family planning for a maximum of 2 to 5 years of use. Most of these women have sufficient knowledge about the use of family planning, and the side effects after using family planning in the long term. Based on the results of the research conducted, there is a conclusion which states that from the results of the researchers' calculations regarding the number of birth control users who experience amenorrhea, spotting, increased body weight, and vaginal discharge, they are still in normal numbers, with sufficient knowledge from respondents about family planning and how to use it. handle the side effects that occurred for 3 months at TPMB Siti Alfiyah..